Response of mungbean to different level of macro and micronutrient - Bithy, Parvin Akter (Research in Agriculture Livestock and Fisheries, 2024)
An experiment was carried out at the Agronomy Farm of Sher-e-Bangla Agricultural University, Dhaka during Kharif I season 2024, in order to investigate the effects of zinc and calcium on growth and yield of BARI mug 6. Three levels of zinc (0, 1.5 and 3.0 kg ha-1) and four levels of calcium (0,50,75,100 ppm) were applied for the study. BARI mug 6 was used as plant material. The experiment was set up in randomized complete block design with three replications. Almost all the parameters were significantly influenced by different levels of Zn, Ca and their combinations. Considering interaction of Zn and Ca, the highest plant height (66.29 cm), number of flowers plant-1 (29.00) and number of nodules plant-1 (29.32) were obtained from the treatment combination of Zn3Ca4 where the highest chlorophyll content (Chl-a = 1.03 μg g-1, Chl-b = 1.32 μg g-1 and total = 2.48 μg g-1) were obtained from the treatment combination of Zn3Ca3.The highest dry weight plant-1 (24.70 g), number of pods plant-1 (23.24), number of seeds pod-1 (11.86), number of fertile seeds pod-1 (10.00), pod length (cm) (7.80), weight of 1000 seed (46.49), weight of seeds plant-1 (12.69), seed yield (1257 kg ha-1), stover yield (1566 kg ha-1), biological yield (2923 kg ha-1) and harvest index (43.87%) were achieved from the treatment combination of Zn2Ca3. Res. Agric. Livest. Fish. Vol. 11, No. 2, August 2024: 159-171